PERSONAL BRANDING, SOCIAL MEDIA MARKETING, DAN WORD OF MOUTH DALAM MENINGKATKAN BUYING DECISION PADA KONSUMEN E-COMMERCE SHOPEE - Putra, Bagus Nyoman Kusuma; Vipraprastha, Tiksnayana (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
ABSTRACT In doing a good marketing effort to attract consumer purchasing decisions is to pay attention to personal branding, social media marketing and word of mouth. With the increasing number of purchasing decisions, especially those aimed at E-Commerce Shopee consumers, this study aims to find out the relationship between personal branding, social media marketing and word of mouth on purchasing decisions. This study involved 130 respondents. There are three hypotheses put forward for in-depth analysis. There are differences in previous studies, the results state that there is a relationship between personal branding, social media marketing and word of mouth on purchasing decisions. This research provides a number of implications, limitations and directions for further research. Keywords: personal branding; social media marketing; word of mouth; buying decision ABSTRAK Dalam melakukan usaha pemasaran yang baik untuk menarik buying decision konsumen adalah dengan cara memperhatikan personal branding, social media marketing dan word of mouth. Dengan semakin meningkatnya buying decision terutama yang ditujukan pada konsumen E-Commerce Shopee, penelitian ini bertujuan untuk mencari tahu hubungan personal branding, social media marketing dan word of mouth terhadap buying decision. Penelitian ini melibatkan 130 responden. Ada tiga hipotesis yang dikemukakan untuk dianalisis secara mendalam. Terdapat perbedaan pada studi sebelumnya, hasil menyatakan bahwa adanya hubungan antara personal branding, social media marketing dan word of mouth terhadap buying decision. Dalam penelitian ini memberikan sejumlah implikasi, batasan dan arahan untuk penelitian selanjutnya. Kata kunci: personal branding; social media marketing; word of mouth; buying decision